PENGARUH PESAN KAMPANYE PROGRAM GERMAS (GERAKAN MASYARAKAT HIDUP SEHAT) PUSKESMAS HARAPAN RAYA TERHADAP GAYA HIDUP SEHAT MASYARAKAT KECAMATAN BUKIT RAYA KOTA PEKANBARU - Sri Wahyu; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Pekanbaru City, which holds the status of the capital city of Riau Province, is faced with the problem of disease cases, which are related to an unhealthy lifestyle. Based on the Central Statistics Agency of Pekanbaru City, Bukit Raya District is one of the sub-districts ranked second in terms of disease cases in Pekanbaru City. In addition, the distribution of GERMAS is mostly found in Bukit Raya Subdistrict, seen in the holding of GERMAS at CFD (Car Free Day) in Bukit Raya Sub-district and the distribution of GERMAS billboards, banners and campaign brochures. The purpose of this study was to know at a glance the effect of the GERMAS campaign message (a movement for a healthy living community) Harapan Raya Community Health Center on the healthy lifestyle of the people of Bukit Raya District.This study uses quantitative research methods, with data analysis techniques, namely through distributing questionnaires directly to the people of Bukit Raya Subdistrict with a population of 27,333 people and the number of samples taken is 100 respondents calculated using the Slovin formula and determined by accidental sampling technique. The results of this study indicate the value of the regression coefficient in this study is Y = 8,072 + 0,770 X Meanwhile tcount (8,981) is greater than ttable (1.984). Based on the statistical calculations obtained, the hypothesis for this study is that Ha there is a significant influence between the message of the GERMAS campaign (X) the healthy lifestyle of the people of Bukit Raya District (Y). So it means that Ha is accepted and H0 is rejected. Furthermore, the coefficient of determination (Rsquare) is 0.451. This can state that the life of the people of Bukit Raya Subdistrict is 45.1%, which means that the message of the GERMAS campaign is temporary obtained by other variables that are not included in this study. Keywords: Campaign Message, GERMAS, Healthy Lifestyle